Gingivitis and associated factors in preschoolers from community homes in Valle del Cauca - Corchuelo-Ojeda, Jairo; Soto-Llanos, Libia (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: The aim of this study was to evaluate the prevalence of gingivitis and associated factors in preschoolers from community homes in 6 municipalities of Valle del Cauca, Colombia. Methods: analytical transverse study in 982 children from 11 community homes selected by simple random sampling; the presence of gingivitis and the community bacterial plaque index (CBP) were recorded. Results: a gingivitis prevalence of 30.8% and a bacterial plaque index of 41.3% (CI95% 40.4-42.5) were found. A plaque level of 2.2% was considered acceptable. The highest prevalence of gingivitis was related to the Afro-descendant population, preschoolers’ poor oral hygiene, and poor oral health knowledge among the mothers from evaluated community homes. Conclusions: A high prevalence of gingivitis was found in connection to high levels of bacterial plaque and the presence of caries, reflecting the health services’ poor response to preschoolers’ oral problems.